2013
DOI: 10.1038/bjc.2013.8
|View full text |Cite|
|
Sign up to set email alerts
|

Serum microRNA expression profile: miR-1246 as a novel diagnostic and prognostic biomarker for oesophageal squamous cell carcinoma

Abstract: Background:Recent studies have demonstrated that microRNAs (miRNAs) are stably detectable in blood and can serve as useful biomarkers for cancer.Methods:We performed an miRNA array using serum samples obtained from oesophageal squamous cell carcinoma (ESCC) patients or healthy controls. MiR-1246 was the most markedly elevated in ESCC patients. Therefore, miR-1246 was selected as a candidate for further analysis. The serum miR-1246 level in 46 healthy controls and 101 ESCC patients was evaluated and compared am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
207
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(224 citation statements)
references
References 47 publications
17
207
0
Order By: Relevance
“…Recent independent profiling studies found circulating or tissue-associated miR-1246 to be differentially expressed in several malignancies (21)(22)(23). Importantly, given that the putative miR-1246 is very likely a result of false mapping of RNU2-1f, all of the results reported herein concern circulating RNU2-1f rather than miR-1246 (16,18 ).…”
Section: Discussionmentioning
confidence: 61%
“…Recent independent profiling studies found circulating or tissue-associated miR-1246 to be differentially expressed in several malignancies (21)(22)(23). Importantly, given that the putative miR-1246 is very likely a result of false mapping of RNU2-1f, all of the results reported herein concern circulating RNU2-1f rather than miR-1246 (16,18 ).…”
Section: Discussionmentioning
confidence: 61%
“…In particular, miR-485-5p expression was inversely correlated with TNM stage and metastasis in HCC samples (25). Serum miR-1246 was significantly higher in primary colorectal and esophageal cancer patients compared with in healthy controls and significantly correlated with TNM stage (27,28). Therefore, these three miRNAs (miR-485-5p, miR-1246 and miR-1275), may be biomarkers for cervical cancer with lower specificity.…”
Section: Discussionmentioning
confidence: 98%
“…The study by Mar-Aguilar et al confirmed the upregulation of miR-382 in the serum of patients with breast cancer; a sensitivity of 94.40% and a specificity of 90.00% was found for the diagnosis of breast cancer (24). A study by Li et al showed that miR-382-5p expression was significantly downregulated in patients with ductal carcinoma in situ (25), while miR-1246 was demonstrated to exhibit high expression in colorectal cancer (26), esophageal squamous cell carcinoma (27), cervical carcinoma (28), hepatocellular carcinoma (29) and other cancers. The expression profiles of miRNAs in the serum and tissues are different.…”
Section: A B C Dmentioning
confidence: 89%